Teachers’ Insights on the Development of Personal Competence of Pupils with Visual Impairments in Music Schools - Žuk-Butkuvienė, Aleksandra (Jaunųjų mokslininkų darbai, 2021)
According to the legal acts of the European Union and Lithuania regulating the aims and peculiarities of the organization of education, non-formal education and learning and educational assistance for pupils with special educational needs, scientific research of Lithuanian and foreign authors, it can be stated that musical activity for pupils with special educational needs benefits revealing and strengthening of their personal competence. However, the research on development of personal competence through non-formal and formal education, complemented with music and art programs for children with special needs, especially students with visual impairments, is insufficient.The aim of the research is to reveal teachers’ insights on the development of personal competence of pupils with visual impairments in music schools. To reveal the aim of this work and to reach its goals qualitative research based on qualitative content analysis is used. The methods to collect information are: semi-structured interviews and monitoring.Personal competence can be defined as corresponding components, that make up  three types of skills: self-understanding (well-being, self-expression, independence), self-evaluation (self-assessment, self-esteem, self-confidence), self-control (self-regulation, decision-making, responsibility, sociability). The results of the semi-structured interview with 5 teachers suggest that purposeful development of personal competence of pupils with visual impairments can help to create and implement already existing social skills, to strengthen and expand them with practical experience. Music schools have an opportunity to educate pupils with visual impairments by individualizing curricula, enabling them to disclose their talents and meeting their individual needs for self-expression, nurturing innate powers, preparing for autonomous life, understanding common values, which will later be used as a framework for their future lives.
Keywords: personal competence; visual impairments; non-formal education